Investing in an emerging supplier to encourage product innovation under market competition and R&D uncertainty - Junwei Zhao; Huiqin Zhang; Yuxiang Zhang; Yexia Zhang; Anhang Chen (Humanities & Social Sciences Communications)
Abstract With the intensification of economic globalization and market competition, manufacturers collaborate with upstream enterprises to build a supply chain with close technical relationships. However, the technology spillover effects caused by direct investment in established suppliers often lead to competitors free-riding, thereby weakening the incentive for enterprises to invest. Consequently, more and more manufacturers tend to invest in emerging suppliers to prevent technology spillovers while also triggering competition among suppliers to gain procurement and competitive advantages. This study explores how a manufacturer chooses the optimal investment strategy to develop an emerging supplier in the face of varying market competition intensities and R&D uncertainty. The research considers three investment strategies: equity investment, loan investment, and cost-sharing, and analyzes the implementation effects of these strategies. We find that in highly competitive markets, the manufacturer tends to choose loan investment to reduce risk; interestingly, in moderately competitive markets, the manufacturer opts for equity investment when the shareholding ratio is small; and in less competitive markets, the manufacturer prefers equity investment when the shareholding ratio is large. Additionally, an increase in the probability of R&D success may make the manufacturer more inclined to adopt loan investment. From the perspective of product innovation, both equity investment and cost-sharing are more effective in motivating the emerging supplier to engage in product innovation, primarily depending on the depth of the manufacturer’s equity. However, an increase in the probability of R&D success tends to inhibit such innovative activities. Importantly, we also find that the manufacturer chooses not to invest in the emerging supplier when the competition intensity exceeds a certain threshold. This highlights the critical role of competition intensity in driving enterprises’ investment decisions. These findings can provide valuable managerial insights for the innovative development of supply chains.